2013
DOI: 10.1515/hmbci-2012-0035
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal rat osteoblasts bioconvert testosterone to non-phenolic metabolites with estrogen-like effects on bone cell proliferation and differentiation

Abstract: Testosterone (T) restores bone mass loss in postmenopausal women and osteoporotic men mainly through its bioconversion to estradiol (E2). In target tissues, T is also biotransformed to the A-ring-reduced metabolites 3α,5α-androstanediol (3α,5α-diol) and 3β,5α-androstanediol (3β,5α-diol), which are potent estrogen receptor (ER) agonists; however, their biological role in bone has not been completely elucidated. To assess if osteoblasts bioconvert T to 3α,5α-diol and to 3β,5α-diol, we studied in cultured neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
1
0
1
Order By: Relevance
“…Since both E1-S and DHEA-S elicit effects similar to E2, which are blocked by STS inhibition (Selcer and Difrancesca, 2012 ; Dias and Selcer, 2014 ), these studies demonstrate that conjugated steroids are activated and that DHEA is converted to E2. Studies in rat osteoblast with [14C]T demonstrated that T is converted by SRD5As and AKR1Cs to 3α/3βDIOLs, which induce proliferation via activation of ER (and not AR) (Enríquez et al, 2013 ).…”
Section: Intracrinology In Peripheral Tissuesmentioning
confidence: 99%
“…Since both E1-S and DHEA-S elicit effects similar to E2, which are blocked by STS inhibition (Selcer and Difrancesca, 2012 ; Dias and Selcer, 2014 ), these studies demonstrate that conjugated steroids are activated and that DHEA is converted to E2. Studies in rat osteoblast with [14C]T demonstrated that T is converted by SRD5As and AKR1Cs to 3α/3βDIOLs, which induce proliferation via activation of ER (and not AR) (Enríquez et al, 2013 ).…”
Section: Intracrinology In Peripheral Tissuesmentioning
confidence: 99%
“…La pronta (15 min) y abundante formación del metabolito 5α-GSD, seguida de un descenso muy marcado a través de los subsecuentes tiempos de incubación y, en forma concomitante, el incremento en la formación de 3β,5αGSD y de su epímero 3α, aunque en menor proporción, es acorde con el concepto de que en esteroides naturales como la testosterona, la molécula 5α-reducida es un intermediario obligatorio en la biosíntesis de los tetrahidros 3α y 3β (Pérez- Enríquez et al, 2013). De acuerdo a los resultados obtenidos, en la Figura 8 se representa el destino metabólico de la molécula de GSD en las células MCF-7 de cáncer de mama.…”
Section: Discussionunclassified